A New Investigation of Prey-Predator Interactions Among Bacterial Species and Protozoa Under Atangana-Baleanu-Caputo Derivative - Partohaghighi, Mohammad; İnç, Mustafa; Qureshi, Sania; Hincal, Evren; Shaikh, Asif Ali; Gokbulut, Nezihal (Natural Sciences Publishing, 2024)
During the current investigation, we examine the impact of a contagious disease on the growth of the ecological system. We study a non-integer-order predator-prey system by applying the Atanagana-Baleanu-Caputo (ABC) derivative. Indeed, an effective numerical technique is exercised to discover the system’s dynamic behavior using different values of the fractional-order parameter. Moreover, the existence of the results is given utilizing the fixed-point theorem. Also, diagrams via numerical simulations of the approximate solutions are explained in different dimensions. Finally, the analysis carried out in this manuscript helps us understand the several interactions among different species and protozoa that commonly occur in bio- and ecological systems. © 2024 NSP Natural Sciences Publishing Cor.
Keywords: fixed point analysis; fractional calculus; Mittag–Leffler kernel; predator-prey system